Feminism, the family, and the politics of the closet lesbian and gay displacement - Calhoun, Cheshire; Oxford eBooks (Oxford : Oxford University Press, 2000)
This text is about placing sexual orientation politics within feminist theorizing. It is also about defining the central political issues confronting lesbian and gay men.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Lesbian feminism; Lesbians -- Political activity; Gay men -- Political activity; Sexual orientation -- Political aspects; Electronic books